Effectiveness of the Application of Good Governance Principles in Vehicle Testing Services at the Gorontalo City Transportation Office - Nurain M Kuku; Marwan Djafar; Sumiyati B (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to determine the effectiveness of the application of the principle of good governance in vehicle testing services at the Gorontalo City Transportation Agency and the factors that hinder the application of the principle of good governance in these services. This study uses a type of empirical legal research with a sociological juridical approach. The data sources used consisted of primary data obtained through observation and interviews with the Gorontalo City Transportation Office and the community using motor vehicle testing services, and secondary data obtained through literature studies of laws and regulations, books, and journals related to research. The data analysis technique is carried out qualitatively by describing the results of the research systematically. The results of the study show that the application of good governance principles in vehicle testing services at the Gorontalo City Transportation Office has been running quite well. This can be seen from the application of the principle of transparency through the disclosure of service information, the principle of accountability through the implementation of duties according to standard operating procedures, and the principle of responsiveness through officer services to the community. However, the effectiveness of services is still not optimal because there are still delays in services, vehicle queues, and service infrastructure facilities have not been maximized. The factors that hinder the application of the principle of good governance in vehicle testing services consist of human resource factors and infrastructure factors. The limited number of vehicle testing officers and the inadequacy of testing equipment are obstacles in the implementation of motor vehicle testing services at the Gorontalo City Transportation Office.